Pelatihan Membaca Menggunakan Metode Fonik untuk Melatih Kemampuan Membaca bagi Anak Usia Dini - Isna Amanaturrakhmah (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
Reading training using the phonics method is organized to explore methods that are appropriate to early childhood learning styles. This activity was organized for study groups in the village of Segeran Kidul, Juntinyuat sub-district, Indramayu district. The target of the activity is study group participants who are able to spell and sound syllables, but still have difficulty in reading. This report is presented qualitatively and analyzed descriptively. The results of the activity showed that the training participants were enthusiastic in trying and learning to read using the phonics method. 7 participants consisting of 5-6 years old showed reading ability according to their age category. while 2 participants aged 7 years did not show the ability to read according to their age category. They can only spell letters based on syllables. To obtain a significant increase in reading skills requires intense practice and habituation.